Is there a tiller morphology ideotype for yield differences in perennial ryegrass (Lolium perenne L.)?. (17th November 2016) - Griffiths, W. M.; Matthew, C.; Lee, J. M.; Chapman, D. F.
Abstract: The objectives of this study were to measure the variability in 'realized' tiller morphology and identify whether there are emergent generalizations about a tiller ideotype for productivity or survival. Morphological traits during the vegetative growth stage were measured for 2 years in the field for eight perennial ryegrass cultivars: six diploid and two tetraploid cultivars under low and high nitrogen fertilizer (50 and 225 kg N ha −1 year −1 respectively). Traits measured were lamina width, length and area; pseudo‐stem length and diameter; an index of tiller shape; tiller dry weight; tiller density; and herbage mass. Almost all the traits differed significantly between cultivars and significant correlations were found between the 2 years. Principal component analysis identified that tiller morphology and dry‐matter yield were independent. No trait associations indicating alternative cultivar‐specific tiller morphologies were detected but cultivars differed in tiller size. The patterns of change between the 2 years indicated a possible morphological trajectory as swards age. The genetic compensatory relationship between tiller size and density had a 1:1 slope, indicative of constant yield. This implies that larger tillers would be more leafy, and higher leafiness of tetraploid over diploid cultivars was confirmed by the leaf:non‐leaf ratio and tiller shape index.